Purwarupa Robot Pipe Following Pendeteksi Kebocoran Gas Internet of Things Berbasis Web dan Aplikasi Android - Ahmad Setiaji; Adrijani Sumarahinsih; Subairi Subairi (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2022)
Indonesia is one of the largest producers/producers and consumers of natural gas in the world. The large demand for gas makes the gas industry continue to produce. Gas pipes used in industry have very large sizes. This makes it difficult for workers to carry out pipe maintenance. In the gas production process, there is the possibility of gas leaks that threaten the safety of the workers. Therefore, this research is expected to help workers. A mobile pipe following robot that can detect gas leaks. Robot control can be done manually and automatically. The robot is also based on the internet of things that can be controlled via an android application and the gas leak data will be stored in a web database.